2001
DOI: 10.1007/s394-001-8352-2
|View full text |Cite
|
Sign up to set email alerts
|

Animal nutrition and acid-base balance

Abstract: In domestic animals, acid-base balance may be influenced by nutrition. The major research effort in this area has been made on the prevention of hypocalcemic postparturient paresis in dairy cows. This disorder is caused by the sudden increase of calcium secretion into the colostrum. The manipulation of the dietary cation-anion difference makes it possible to maintain the cows in metabolic acidosis during the critical period that precedes calving, presumably via a mechanism that involves the strong ion differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0
2

Year Published

2004
2004
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 39 publications
2
28
0
2
Order By: Relevance
“…The effect of acidification on mineral metabolism, especially renal excretion of major minerals as described in the present study in rabbits, has been demonstrated in other monogastric species before (Jaffe et al., ; Sartorius et al., ; Langendorf and Lang, ; Burnell, ; Kraut et al., ; Ching et al., ; Cooper et al., ; Riond, ; McKenzie et al., ; Topliff, ; Chen and Shan, ). As shown in Fig.…”
Section: Discussionsupporting
confidence: 80%
“…The effect of acidification on mineral metabolism, especially renal excretion of major minerals as described in the present study in rabbits, has been demonstrated in other monogastric species before (Jaffe et al., ; Sartorius et al., ; Langendorf and Lang, ; Burnell, ; Kraut et al., ; Ching et al., ; Cooper et al., ; Riond, ; McKenzie et al., ; Topliff, ; Chen and Shan, ). As shown in Fig.…”
Section: Discussionsupporting
confidence: 80%
“…A debate regarding the relationship between dietary protein and bone health has unrolled over more than 50 years. Animal, epidemiological, and clinical works have corroborated that high protein intakes can impose a small, but chronic, metabolic acid load, 1–3 and that this acid load may cause bone loss 4–6 . Indeed, urinary calcium losses are unequivocally induced by high protein intakes 7 .…”
Section: Introductionmentioning
confidence: 98%
“…Dietas ácidas induzem a liberação de cátions (incluindo o cálcio) do osso para o sangue para corrigir seu pH. A acidose metabólica estimula primeiro a dissolução mineral e depois a reabsorção óssea mediada por células devido à maior excreção de cálcio pelos rins (Riond, 2001). Essa perda de cálcio resultaria em menor mineralização óssea e, consequentemente, menores peso, densidade e IPC.…”
Section: Resultsunclassified